(untitled) (Research, Society and Development, 2021)
The research aims to carry out a literature review on studies that applied nutritional conducts in enteral nutrition in clinical practice for the treatment of cancer patients and report the benefits of this type of therapy. This is an integrative literature review based on the following guiding question: Is enteral nutritional therapy beneficial for patients undergoing cancer treatment? The selection of studies was carried out during the months of October and November 2021, in the following databases: National Library of Medicine (PUBMED), Elsevier Virtual Library (SCIENCE DIRECT) and Virtual Health Library (VHL) via Capes Periodical portal. Initially, the strategy for searching the studies was composed of a combination of controlled descriptors (Nutritional therapy. Enteral nutrition. Benefits. Oncology patients) indexed in the Health Sciences Descriptors (DeCS/MeSH). After the search and selection process using the criteria mentioned in the methodology, 7 articles were selected. The analyzed and discussed studies report significant benefits performed by enteral nutrition in cancer patients, such as limiting weight loss, providing patients with adequate energy intake, meeting increased nutritional demands due to the disease, improvement of immune function and gastrointestinal function, recovery accelerated, reduction of postoperative complications and hospitalization time and improvement of nutritional indicators.